(untitled) (Research, Society and Development, 2021)
Veterinary medicine students receive a multidisciplinary education to have generalist training, and to be able to meet the needs demanded by society. However, most students enter the course with the intention of working in clinics, not knowing other areas. The objective of this research was to analyze the affinity for the food area of ​​students from the veterinary medicine course at Federal University of Fronteira Sul - Campus Realeza. The research was carried out through the application of an online questionnaire, 257 undergraduates and graduates participated in the research. The profile of participants was mostly women (72.4%), young people aged between 20 and 25 years (60.31%) and from the South region (77.8%). And 91.1% of participants said they chose the course by identification and affinity, initially to the areas of clinic or surgery of small and large animals (35.4% and 28.8% respectively). However, 45.1% changed their opinions. Of the participants, 96.9% consumed animal products and 73.9% were aware that the veterinarian could work in the food area, and a linear growth in the responses from the first to the fifth year about working in this area. Thus, it is necessary to carry out educational and informative work in order to raise awareness in the community and encourage students to interact and participate with all possible areas of veterinary medicine, so that they understand the vast field of action.